Answer:
x = 11
Step-by-step explanation:
2x + 34 = 56
2x = 56 - 34
2x = 22
x = 22/2
x = 11
Answer:
3
Step-by-step explanation:
By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
<h3>How to find the inverse of a function</h3>
In this question we have a <em>rational</em> function f(x) and finding its inverse consists in clearing x in terms of f(x). Prior any algebraic handling, we need to apply the following substitutions:
x · (y + 7) = - 2 · y + 2
x · y + 7 · x = - 2 · y + 2
2 · y + x · y = - 7 · x + 2
y · (2 + x) = - 7 · x + 2
By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
To learn more on inverses: brainly.com/question/7181576
#SPJ1
Answer:
Step-by-step explanation:
this is simplify
Answer:
y=7x
Step-by-step explanation:
slope intercept form is y=mx+b.
m is the slope (rise over run) and b is your y- intercept. you leave y as it is. if the line is going down, you have a negative slope. hope this helped :)